Social class differentials in the performance on the the Denver Developmental Screening Test of preschoolers in selected areas of Greater Manila - Andaya, Estela Cantor
PURPOSE OF THE STUDY: This study was undrtaken for two reasons namely: 1. to assess the behavioral development (gross motor,fine motor, language, personal social aspects) of Filipino children ages 13 months to 6 1/2 years through their performance on the DDST, and 2. to determine any significant associative relationship between social class and performance on the DDST by Filipino children.{{{{The main problem was focused on the question: How does the performance on the Denver Developmental Screening Test of Greater Manila children coming from lower class compare with the performance of children from the upper/middle class?{{{{Subordinate problems included the following: 1. In what aspects of behavior (personal social, gross motor fine motor, and language) are there similarities or significant differences in terms of advanced performance? 2. In what aspects of behavior are there similarities or significant differences in terms of delayed performance?{{{{SUBJECTS AND SETTINGS: Five hundred sixty-six subjects (287 males and 279 females) comprised the study population. Based on the occupations of Subjects' fathers, 204 upper/middle and 362 lower class Subjects were sampled. This study was done in four areas of Greater Manila: Manila (275), Quezon City (192), Makati (63), and Pasay City (36).{{{{METHODOLOGY: This is a one-shot field study. The explanatory variables include: the independent variable which is socioeconomic status, determined mainly by the occupations of Subjects' fathers. Two social strata are compared, the upper/middle class and the lower class. The dependent variable is childrens' performance on the Denver Developmental Screening Test.{{{{DATA COLLECTION AND ANALYSIS: Data was collected between January 1977 to August 1977. First a district was chosen from each of the four randomly picked areas of Greater Manila, after which house-holds were sampled with in the district. A random start in each district was chosen by this investigator who then went from one street to the other sampling children from every fifth household until the quota for each area was reached.{{{{Data were analyzed utilizing a computer program for Logit Analysis to arrive at the medians and variances which were later converted into days by using the same computer program. Computation for statistical significance was done using the normal test of significance or "Z". Through the chi-square test the goodness-of-fit of the logistic model to the data was determined.{{{{FINDINGS, CONCLUSIONS, RECOMMENDATIONS: Findings are presented in connection with the hypotheses posed.{{{{Relative to the hypothesis that: Upper/middle class and lower class Subjects will differ in their DDST performance pattern, the following are among the finsings obtained: 1. The pattern (ranking) of performance scores are the same for both classes. The greatest number of Subjects are scored "normal" and the least number of scores are "abnormals". "Questionables", and "untestables" occupying intermediate ranking. 2. The Z test for significance, showed that there were about as many upper/middle class children as lower class children who were rated "normal", "untestable" and "abnormal". However, there were significantly more lower class children who wre rated as "questionables" compared to the upper/middle class.{{{{Thus the hypothsis was partially supported by findings.{{{{Relative to the hypothesis that: Children of the upper/middle class will develop earlier in general on the four aspects of behavior, it was found that: 1. The upper/middle class children showed significantly more advanced development in the following behavioral tasks: a. In Language behavior ...
Thesis (Master of Arts in Nursing) -- University of the Philippines.
Keywords: Denver Developmental Screening Test; Child study; Children--Growth.